POLEMIK TAMBANG NIKEL DI PULAU GAG RAJA AMPAT : DITINJAU DARI PERSPEKTIF POSITIVISME HUKUM - Silehu, M Iqbal; Pratiwi, Cekli Setya (PRODI HUKUM TATANEGARA, 2025)
The issue of nickel mining has long been intertwined with legal norms and environmental ethics. The dispute involving PT. Gag Nickel on Gag Island underscores critical legal challenges. PT. Gag initially operated under a 1998 Contract of Work authorized by Soeharto, allowing nickel mining on Gag Island in Raja Ampat Regency. However, Law 41/1999 prohibited mining in protected forests, halting PT. Gag's operations. This was reversed in 2004 when Presidential Regulation 41/2004 granted exemptions to 13 companies, including PT. Gag, for operations predating the law. In 2007, Law 27/2007 further restricted mining on islands smaller than 200,000 hectares, including Gag Island, which spans only 6,069 hectares. Despite this, PT. Gag obtained IPPKH and IUP permits in 2017 from the Ministries of Environment and Energy and Mineral Resources, allowing the resumption of mining activities in violation of both Laws 41/1999 and 27/2007. The controversy escalated in 2024 when the Constitutional Court reaffirmed the prohibition of mining on small islands under Law 27/2007. These regulatory conflicts undermine legal certainty. This study, guided by legal positivism, emphasizes the need to revise conflicting regulations and ensure alignment between local and higher laws. The research adopts a normative juridical methods, statute approach, case approach, and conceptual approach.